Professor Leszek Filipczyński Scientific biography - ETIENNE, J.; RANACHOWSKI, J. (Archives of Acoustics, 1994)
Scientific biography is an accumulation of facts and titles, often so numerous, and so swiftly each other that it is not easy to understand, how a single individual might be able to initiate and perform so much work. Scientific profile should contain more than such a biography: apart from listing the achievements, titles, and awards, it should reflect individual features of a man, and first of all his virtues which should be regarded as a source of his scientific achievements. In the case of Professor Leszek Filipczyński – full member of the Polish Academy of Sciences – there is such a lot of both scientific and organizational achievements, that it is easy to guess what stands behind them: unusual mind, unusual industry, rare ease to contact people, and an exceptional organizational skills.